2021
DOI: 10.1016/j.aninu.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with acidifiers improves the growth performance, meat quality and intestinal health of broiler chickens

Abstract: This experiment was conducted to study the effects of dietary supplementation with acidifiers on the growth performance, meat quality, and intestinal health of broiler chickens. A total of 648 male Arbor Acres broiler chickens at 1 d old were randomly divided into 6 groups, and each group consisted of 6 replicates with 18 broilers per replicate. The dietary treatments were as follows: negative control (NC, the basal diet), NC + antibiotic (enramycin, 8 mg/kg, positive control [PC]), NC + phosphoric acid (PA, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Antibiotic resistance has an undesirable effect on people other than the immediate consumer of the antibiotic [4]. Several research studies on promising alternatives to antibiotics are currently being developed in livestock, such as probiotics [5], acidifiers [6], plant extracts [7], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance has an undesirable effect on people other than the immediate consumer of the antibiotic [4]. Several research studies on promising alternatives to antibiotics are currently being developed in livestock, such as probiotics [5], acidifiers [6], plant extracts [7], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…They are used as an antibiotic alternative that can alter the physiology and lead to the death of pathogenic microorganisms in animals, including poultry [5,6]. Various literatures reveal that antibiotics have better positive effects in modulating metabolism, improving weight gain, feed efficiency and controlling diseases in poultry production [7,8]. However, their continued use in animal nutrition developed antibiotic resistance and drug residues, which resulted in global public health issues and exacerbating poverty in the 21st century [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[27] and salmonella typhimurium-related diseases [29,30]. A meta-analytic study of organic acids confirmed that blends of two or more specific organic acids improved performance, immunity and welfare of birds better than any acid achieved alone [4,8]. For example, Ndelekwute et al studied the effects of four different acidifiers on gut performance and found that organic acids could be used in diets for broilers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the crop and gizzard, the pH of poultrys’ digestive tract is above 5.0 [ 52 ]. In the present study, the optimal pH for DacA and DacB degrading OTA was between 6.5 and 7.5, which happened to be the range of pH of the small intestine.…”
Section: Discussionmentioning
confidence: 99%